Flower development schedule and AGAMOUS‐like gene expression patterns in two morphs of Nigella damascena (Ranunculaceae) differing in floral architecture. (12th June 2015) - Jabbour, Florian; Udron, Mathilde; Le Guilloux, Martine; Gonçalves, Beatriz; Manicacci, Domenica; Nadot, Sophie; Damerval, Catherine
<x xml:space="preserve">Abstract</x> Love‐in‐a‐mist (Nigella damascena) is an annual species of Ranunculaceae native to the Mediterranean Basin, characterized by delicate flowers lying on long lacy bracts. Two floral morphs of N. damascena, designated [P] and [T], differ in the identity and number of perianth organs and in the position of the perianth–androecium boundary on the meristem. They both occur in the wild. Here we describe a precise comparative schedule of floral development in the two morphs. We divided the sequence of developmental events affecting the floral meristem into six stages and related them to the height of the elongating stem and to the time elapsed after the beginning of stem elongation. In addition, we characterized the expression pattern of C‐class genes in floral organs of both morphs in an attempt to better characterize the differences between the two floral groundplans. In the [T] morph an expansion of the expression domain of AGAMOUS (AG) paralogues outside the fertile organs was observed, correlating with the change in identity of the inner perianth organs. Expression of AG‐like genes in the sepal‐like organs suggests these are not identical to true sepals at the molecular level. The morpho‐temporal framework we have defined will allow us to compare various gene expression profiles at targeted developmental stages in both morphs, providing further insight into the molecular control of the floral dimorphism in N. damascena and into the processes underlying the transition from a differentiated (bipartite) to an undifferentiated (unipartite) perianth. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 178, 608–619.